Dekonstruksi Epistemologi Zakat: Analisis melalui Kritik Nalar Arab Muhammad Abed Al-Jabiri - Timbang Apit Afifah; Tri Aldi Winata; Mar’atus Solikhah; Ahmad Romdhoni; Rahmini Hadi (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to deconstruct the epistemology of zakat which has been dominated by the Bayani (textual) approach, causing zakat management to be trapped in ritual dimensions and lacking responsiveness to structural poverty. Using Muhammad Abed Al-Jabiri’s Critique of Arab Reason, this study attempts to offer a Burhani (rational-demonstrative) approach to understanding zakat. The research method used is qualitative with a library research type. The results show that the dominance of Bayani reason in zakat fiqh has resulted in a rigid understanding of asnaf and zakat objects. Through Al-Jabiri’s analysis, zakat needs to be shifted towards Burhani reasoning which emphasizes causality and social benefit (maslahah). The deconstruction of zakat epistemology implies that zakat must be understood not only as a dogmatic obligation but as an economic instrument capable of answering the challenges of the times through measurable productivity. This study concludes that the integration of Burhani reason is necessary to transform zakat from theological normativity to sociological functionality.